Pembelajaran IPAS Berbasis STEM untuk Meningkatkan Literasi dan Numerasi Siswa Kelas IV - Novitasari, Nur Diana; Patonah, Siti; Sukamto, Sukamto (Educatio, 2026)
This study aims to analyze the effect of the STEM approach in science learning on improving the literacy and numeracy skills of fourth-grade students, especially in the material of the state of matter and its changes. Data collection in this study was carried out using multiple-choice tests at the beginning and end of learning. Data analysis was carried out according to quantitative data through calculating the average pre-test and post-test scores, by conducting descriptive statistical analysis tests, classical assumption tests in the form of normality tests, homogeneity tests, and hypothesis tests with the help of SPSS. The average pre-test score before the treatment was 15.05 to 24.68 in the post-test using the PjBL learning method. The results of this study indicate that students' literacy and numeracy skills increased significantly after the application of the STEM approach and the PjBL learning model. This is evidenced by the results of the paired t-test, namely sig <0.05 or 0.000 <0.05. Therefore, it is concluded that the use of the STEM approach has an impact on improving the literacy and numeracy skills of fourth-grade students of SDN 5 Ngawen.